Association of PTP4A3 expression and tumour size in functioning pituitary adenoma: a descriptive study. Issue 3 (2nd July 2020) - Moyano Crespo, Gabriela Deisi; Cecenarro, Laura Anahí; Perez, Pablo; Guido, Carolina; Sosa, Liliana del Valle; Berhard, Celina; Aballay, Laura Rosana; Gutiérrez, Silvina; Petiti, Juan Pablo; Torres, Alicia; Mukdsi, Jorge
Abstract : Background: PTP4A3 is a subclass of a protein tyrosine phosphatase super family and is expressed in a range of epithelial neoplasms. We evaluated PTP4A3 expression and its association with clinicopathological parameters in different types of functioning pituitary adenomas. Methods: A total of 34 functioning pituitary adenomas samples were evaluated in this observational study. PTP4A3 expression was examined by immunohistochemical staining, and, possible correlations between PTP4A3 and some clinicopathological variables were investigated. Results: PTP4A3 was expressed in 19 out of 34 tumours (55%), at the cytoplasmic level of tumorous cells. Moreover, there was significant association (p=0.042) between PTP4A3 expression and tumorous size. Conclusions: PTP4A3 was expressed in more than half of the tumours analysed, with there being a significant association with the tumorous size of functioning adenomas. This allows to speculate that PTP4A3 may regulate tumour growth, although further investigations are necessary to determine if this phosphatase can serve as a biomarker or used as a therapeutic target in pituitary macroadenomas.